2014
DOI: 10.1080/00223980.2014.978253
|View full text |Cite
|
Sign up to set email alerts
|

Is Charismatic Leadership Effective When Workers Are Pressured To Be Good Citizens?

Abstract: Prior research has explored how employees' perceptions of their leaders impact their work attitudes and behaviors. Studies have shown that charismatic leaders motivate individuals to be more engaged and to exhibit more organizational citizenship behaviors. This study considers how a moderator, citizenship pressure, affects how charismatic leaders might inspire their followers to go above and beyond and be more engaged in their work. Using a sample of 243 workers, this study's findings show that charismatic lea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 59 publications
2
18
0
Order By: Relevance
“…For example, employees may feel helping pressure if helping is believed to enhance job security or benefit the organization, if managers expect employees to be good citizens, or if coworkers frequently enact helping behaviors (e.g., Bolino et al., ). Although helping pressure does not necessarily lead to helping behavior, the constructs are often (Bolino et al., ; Horn et al., ), but not always (Lin et al., ), positively correlated.…”
Section: Pressure To Be a “Good Soldier”mentioning
confidence: 99%
See 2 more Smart Citations
“…For example, employees may feel helping pressure if helping is believed to enhance job security or benefit the organization, if managers expect employees to be good citizens, or if coworkers frequently enact helping behaviors (e.g., Bolino et al., ). Although helping pressure does not necessarily lead to helping behavior, the constructs are often (Bolino et al., ; Horn et al., ), but not always (Lin et al., ), positively correlated.…”
Section: Pressure To Be a “Good Soldier”mentioning
confidence: 99%
“…To date, this research has definitively shown that some employees do indeed experience pressure to engage in acts of citizenship. When employees experience this pressure, it tends to exacerbate the fatigue‐inducing nature of citizenship behavior, interfere with the beneficial effects of charismatic leadership, and sensitize employees to the consequences of helping behavior for need satisfaction (Bolino et al., ; Horn et al., ; Lin et al., ). In addition, although citizenship pressure does generally increase the enactment of citizenship behaviors, it can also induce stress and work–family conflict (Bolino et al., ; Liu, Zhao, & Sheard, ).…”
Section: Pressure To Be a “Good Soldier”mentioning
confidence: 99%
See 1 more Smart Citation
“…Charismatic leadership is based on the perceptions that followers have about their leader. Studies have shown that charismatic leaders inspire persons to be involved and to display more structural actions (Horn, Mathis, Robinson, & Randle, 2015).…”
Section: Leadership Stylesmentioning
confidence: 99%
“…Charismatic leaders can cause individuals to be involved and show more organizational citizenship behaviors. Horn et al (2015) wrote:…”
Section: Leadership Stylesmentioning
confidence: 99%